Management : a programmed approach with cases and applications - Kazmier, Leonard J. (New York : McGraw-Hill Book Company, 1980)
This book has been designed as an effective aid to understanding the major functions of management and the skills that lead to managerial success, be it in business firms or other kinds of organizations.
Includes bibliographic references and index.
hza 15/10/2018
Loans
Keywords: Management